Acadiana : Louisiana's Historic Cajun Country - Brasseaux, Carl A. (Book collections on Project MUSE., 2011)
ÔAcadianaö summons up visions of a legendary and exotic world of moss-draped cypress, cocoa-colored bayous, subtropical wildlife, and spicy indigenous cuisine. The ancestral home of Cajuns and Creoles, this twenty-two-parish area of south Louisiana encompasses a broad range of people, places, and events. In their historical and pictorial tour of the region, author Carl A. Brasseaux and photographer Philip Gould explore in depth this fascinating and complex world. As passionate documentarians of all things Cajun and Creole, Brasseaux and Gould delve into the topography, culture, and economy of.